2008
DOI: 10.1038/sj.mt.6300348
|View full text |Cite
|
Sign up to set email alerts
|

Myxoma Virus Oncolysis of Primary and Metastatic B16F10 Mouse Tumors In Vivo

Abstract: Myxoma virus (MV) is a rabbit-specific poxvirus, whose unexpected tropism to human cancer cells has led to studies exploring its potential use in oncolytic therapy. MV infects a wide range of human cancer cells in vitro, in a manner intricately linked to the cellular activation of Akt kinase. MV has also been successfully used for treating human glioma xenografts in immunodeficient mice. This study examines the effectiveness of MV in treating primary and metastatic mouse tumors in immunocompetent C57BL6 mice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
67
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 47 publications
1
67
0
2
Order By: Relevance
“…Improved results have also been seen in immunocompetent animals using an oncolytic herpes virus in combination with the cyclophosphamide to suppress the immune response and provide for prolonged replication of the virus (25,26). Recently, we and others have shown that the combination of myxoma virus plus rapamycin led to enhanced viral replication in vitro and in vivo, and improved efficacy against medulloblastomas (27) and melanoma (28). This led us to investigate the use of oncolytic vaccinia virus in combination with rapamycin or cyclophosphamide therapy for the treatment of experimental models of malignant gliomas.…”
mentioning
confidence: 81%
“…Improved results have also been seen in immunocompetent animals using an oncolytic herpes virus in combination with the cyclophosphamide to suppress the immune response and provide for prolonged replication of the virus (25,26). Recently, we and others have shown that the combination of myxoma virus plus rapamycin led to enhanced viral replication in vitro and in vivo, and improved efficacy against medulloblastomas (27) and melanoma (28). This led us to investigate the use of oncolytic vaccinia virus in combination with rapamycin or cyclophosphamide therapy for the treatment of experimental models of malignant gliomas.…”
mentioning
confidence: 81%
“…2). Although rapamycin in conjunction with other viruses (e.g., myxoma virus, vaccinia virus, or adenovirus) augment oncolysis (23,(33)(34)(35)(36), the molecular mechanism by which this process occurs remained elusive. Autophagy and the antiangiogenic effect induced by rapamycin were postulated to promote viral oncolysis (35,37).…”
Section: Discussionmentioning
confidence: 99%
“…Few have used immunocompetent models (23)(24)(25)(26). We have reported promising efficacy of MYXV in immunocompromised brain tumor models (5,14,15); there is one report of MYXV in an immunocompetent model of melanoma (16). The evaluation of an oncolytic virus in immunocompetent setting is important because both the innate and the acquired immune system may dramatically modulate oncolytic efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…We discovered that myxoma virus (MYXV) was oncolytic for several human cancers (5,(13)(14)(15)(16). It is promising for human therapy because its genome has been sequenced, it is simple to engineer, its natural tropism is highly restricted to European rabbits (Oryctolagus cuniculus), and there is no acquired viral immunity in humans (17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation